Influence of the Initial Fiber Orientation on the Weld Strength in Welding of Glass Fiber Reinforced Thermoplastics - Isabel Fiebig; Volker Schoeppner (International Journal of Polymer Science)
The welding factors are significantly lower in welding of fiber reinforced thermoplastics than in welding of unreinforced thermoplastics due to the fiber orientation in the weld. This paper presents results from investigations on the influence of the initial fiber orientation on the weld strength in hot plate and vibration welding for glass fiber reinforced polypropylene and polyamide 6. Injection molded specimens are compared to specimens with main initial fiber orientation being longitudinal and transverse to the joining direction. The results of CT analysis of the fiber orientation in the weld show the opportunity to achieve a higher weld strength by using specimens with fibers being initially oriented longitudinally to the joining direction. The influence of the initial fiber orientation in the parts to be welded on the weld strength in hot plate welding is more distinct than in vibration welding.